A constituição da identidade profissional do formador do curso de Pedagogia na Unifesp Campus Guarulhos - Amaro, Amanda Martins [UNIFESP] (2019)
The constitution of the professional identity of the teacher trainer is a very complex subject that is related not only to the construction of professional life and your job, but also to the personal life of each individual that traces specific paths to become a teacher trainer. This is a field that has not yet been explored (PASSOS, 2018), which has aroused our interest in understanding, through life histories of these professionals, how the teacher´s identity of the Pedagogy course of a Public University is constituted. With the development of the research we seek to know and analyze the life and training trajectories of some teacher trainers who work in the course of Pedagogy of UNIFESP Campus Guarulhos; to identify the influences of the teaching institution on the constitution of the teacher's professional identity of the teacher trainer and to reveal the aspects that characterize the (re) configurations in the identity, the processes of attribution and belonging of the teacher trainers throughout their professional trajectories. For this, we made a brief historical rescue of the creation of the University in Brazil, and the course of Pedagogy (SCHEIBE e AGUIAR, 1999; SAVIANI, 2008; BRZEZINSKI, 1996; SILVA, 2006; SILVESTRE e PINTO, 2017), besides the related studies and the bibliographic review about the subject studied. We base our research theoretically on the specificity of teaching in Higher Education in (CUNHA, 2006; RIBEIRO, 1975; VEIGA, 2006; PIMENTA e ANASTASIOU, 2002) and trainer teacher education studies (PASSOS 2007, 2018; COSTA, 2011; MIZUKAMI, 2006; HOBOLD, 2015). Subsequently, we held discussions and studies on the constitution of the professional identity of the teacher trainer, in which the socialization processes were approached (DUBAR, 1997, 2005; MARCELO, 2009; PLACCO 2010). Based on a qualitative approach, the research data were produced through semi-structured interviews with five teachers from the Department of Education of UNIFESP Campus Guarulhos, organized and analyzed in three categories under prose analysis (ANDRÉ, 1983). The results revealed that the professional identity of the teacher trainers was constituted throughout their personal and professional trajectories through the socialization with the other: the social imaginary, the student and the other trainers. Participating trainers are aware of this social imaginary, on the opinion of some colleagues from other areas and about the fact that the teacher is not valued in society. However, the data revealed that being in UNIFESP has another dimension, because they perceive themselves as trainers and there is identification and belonging with the Pedagogical Project of the Pedagogy Course and its theoretical and practical nature, the conception of curricular stages having as one of the assumptions the immersion in the Pedagogical Residence Program, its partnership with public schools and collaborative work. We identified which choices and paths each research participant made until he became a teacher trainer, we also highlight the influence of the institutional context as a locus in its identity constitution. We also observe that the professional identity goes through moments of deconstruction and reconstruction and, among its indicators, we highlight: the conscious and belonging of being a trainer, understanding the process of sharing and collaborative work, awareness of the benefits of interaction (self and others) and ongoing forCourse of Pedagogy.mation.